Finite element simulation of equal channel angular pressing: effect of die angle and number of passes - Dayangku Noorfazidah, Awang Sh'ri; Muhammad Abdul Hisyam, Abu Hassan; Zahiruddeen Salam, Zahari; W. S., Wan Harun (Universiti Malaysia Pahang, 2019)
Equal channel angular pressing (ECAP) is one of the popular severe plastic deformation processes used to produce bulk nanostructured materials. The degree of homogeneity of nanostructured is affected by various die parameters. In this paper, the effect of internal die angle (ϕ) and number of passes (N) on the strain behaviour of Aluminium Alloy 6061 (AA6061) during ECAP was investigated by using three-dimensional finite element analysis. The effect of number of passes and die angle on the homogeneity within the workpiece was analysed in terms of contours, radial view contour and inhomogeneity index. The analysis is done by comparing workpiece extruded up to 8 passes at die angle of 120° and 126°. It is observed that the resulting strain is higher at 120° die. However, the inhomogeneity index is decreasing in a similar pattern in both dies. The simulation results shed some lights on the optimum design of ECAP die for homogeneous microstructure.